Development of the Brainstorming, Exploring, Talking About, Applying (BETA) Learning Model to Improve Social Studies Students' Critical Thinking - Anto, Ruli; Lasmawan, I Wayan; Parwati, Ni Putu Yuniarika; Suarsika, I Made Agus; Lase, Indah Permata Sari (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2024)
This research aims to develop a learning model Brainstorming, Exploring, Talking about, Applying (BETA) which is effective for every online and offline learning process and a combination of both. The research personnel involved 3 lecturers and 8 students from the English Language Education study program and the History Education study program, FKIP Mahasaraswati University Denpasar. Method research and development (R&D) is used to develop the BETA learning model. Research on the development of the BETA model has been carried out in several stages, namely model development, model testing and implementation of the learning model in the classroom as well as implementation of the BETA model through E- Learning. The BETA model can be implemented by teachers well in the classroom according to the stages of implementing the model, so that students' critical thinking abilities can be improved. It is hoped that research can be carried out on an ongoing basis to apply the BETA learning model in other schools with the aim of introducing the learning model widely in society so that it can improve students' critical thinking abilities. Developing E-Learning better so that it can reach all groups of teachers and students who use E-Learning.